The Relationship Between Knowledge And Attitude With High Risk Pregnancy At Desa Sihotang Hasugian Habinsaran, Kecamatan Parlilitan In 2020 - Fransiska Riati Nova Simbolon (International Archives of Medical Sciences and Public Health, 2022)
A high risk pregnancy is a pregnancy that has a higher risk and is greater than normal in general pregnancy (both for the mother and the baby) with the risk of illness or death before or after the process of the copy. Research aims to know the relationship of knowledge and attitudes with a high risk of pregnancy in the village Sihotang Hasugian directly Habinsaran subdistrict Parlilitan year 2020.This research uses crossectional design. The population in this study is the entire trimester of pregnant women I working area Puskesmas as much as 131 people and samples using 57 people. Data analysis using Chi Square test. The results of the Chi Square test show the results of a knowledge relationship (P = 0,003), attitude (P = 0,000) with a high risk pregnancy. For pregnant women. It is hoped that the expectant mother will take the time to visit the health services such as village midwives, clinics, health centers to conduct a pregnancy check so you can know the condition of the mother and fetus and can be done with pregnancy prevention efforts.